H2 production from ethanol steam reforming using metallic nickel hollow fiber membrane reactor - Lu, Z.; Yuan, C.; Li, C.; Geng, G.; Song, J.; Yang, N.; Kawi, S.; Tan, X.; Sunarso, J.; Liu, Shaomin (2025)
Membrane catalysis is recognized as an ideal technology for H2 production given its potential to integrate the production and separation into one unit. Recent research has pivoted to utilizing nickel (Ni) as an alternative membrane material to Pd and its alloys considering its high stability and low cost, as Ni also possesses H2 adsorption and separation capabilities. In this work, gastight Ni hollow fiber membranes (NiHFMs) were prepared using the combined phase inversion and sintering technique, which was subsequently assembled into a membrane reactor for the H2 production via liquid biomass (ethanol) steam reforming (ESR). The influence of temperature, feed flow rate, sweep gas flow rate, and steam/ethanol (S/E) molar ratio on the ESR performance of the metallic NiHFM reactor were systematically investigated. The metallic NiHFM reactor exhibited excellent ESR catalytic activity, as well as stability, and effective H2 separation capability. At 900 °C, S/E of 3, aqueous ethanol solution feed of 18.389 μL min−1, and N2 sweep of 30 mL min−1, the conversion of ethanol remained stable at 94 % over 180 h. Moreover, the H2 yield reached 45–50 %, and the H2 flux was consistently stabilized at 0.55–0.58 mL cm−2 min−1 under sweep gas mode at ambient pressure. The inspiring long-term operational stability results underscore the potential of the metallic NiHFM reactor in ESR applications, paving the way forward for the direct production of H2 with high-purity from renewable energy sources.